Development of a Novel β-Type Zr-25Ta-5Ti Alloy - Saraiva, Edriely de Oliveira [UNESP]; de Almeida, Gerson Santos [UNESP]; Zambuzzi, Willian Fernando [UNESP]; Kuroda, Pedro Akira Bazaglia; Grandini, Carlos Roberto [UNESP] (Springer Nature, 2024)
This study aims to produce a novel zirconium alloy containing 25 wt.% tantalum and 5 wt.% titanium (Zr-25Ta-5Ti) as a biomaterial. The proposed Zr-25Ta-5Ti was prepared in an arc-melting furnace and subjected to annealing heat treatment at 1000 °C for 24 h to homogenize the microstructure and relieve residual melting stresses. After annealing, the alloy was submitted by hot-rolled process conformation to produce regular material. Chemical composition analyses show that the Zr-25Ta-5Ti alloy has good quality and homogeneity. The homogenization heat treatment increased the density of the Zr-25Ta-5Ti alloy (7.6 → 7.8 g/cm3) due to the formation of the α phase. Structural and microstructure characterization data showed that the Zr-25Ta-5Ti alloy has α, β, and ω phases as a crystalline structure, where the homogenization heat treatment promoted the segregation of the Ta element at the grain boundaries of the β structure, and as a consequence, promoted the formation of the α phase. The hardness of the alloy is superior to titanium and zirconium elements (499 ± 5 HV for as-cast condition and 272 ± 7 HV for the annealed condition). Finally, the Zr-25Ta-5Ti alloy has low values of elastic modulus (86 ± 5 GPa for hot-rolled alloy) compared to commercial metallic biomaterials and biological tests indicated that alloys are not cytotoxic. Thus, taken the data together, this study brings Zr-25Ta-5Ti as a novel biomaterial to be used in biomedical applications.
Keywords: biocompatibility; biomaterials; bone; cell; cytotoxicity; zirconium alloys